Integration of Spatial and Social Analysis for Safe Sanitation in Cemorokandang Urban Village to Support the Achievement of Sustainable Development Goal 6.2.1 - Nike Poerbyanti; Hartati Kartikaningsih; Mufidah Afiyanti (Postgraduate, University of Mataram, 2026)
Safe sanitation is crucial for protecting public health and the environment, particularly in densely populated urban areas where inadequate facilities heighten contamination risks. Cemorokandang Urban Village represents such a vulnerable area, requiring a comprehensive assessment to inform local sanitation planning. This study evaluates the condition of safe sanitation and identifies spatial and social factors influencing its achievement using a mixed-method approach that integrates surveys, field observations, water quality testing, and GIS-based spatial analysis. Primary data covered household sanitation facilities, open defecation practices, and water quality, while secondary data were obtained from local institutions. Findings indicate that although all households have toilets with domestic wastewater systems, only 3,25% (211 of 6.497 buildings) met safely managed sanitation criteria despite 96.75% having adequate facilities. Spatial analysis reveals significant variation in sanitation risk across neighborhoods, strongly linked to differences in education, income, and community behavior. Communities with stronger socio-economic capacity demonstrate better understanding and adoption of safe sanitation practices, supported by training and balanced gender participation. Integrating spatial and social data provides a detailed picture of local challenges and supports the design of community-based, location-specific, and gender-responsive interventions. The study recommends targeted actions in high-risk areas, strengthened behavioral training, and inclusive financing mechanisms to accelerate progress toward Sustainable Development Goal 6.2.1.